Evaluation of postoperative refractive error correction after cataract surgery. - Ellen Konadu Antwi-Adjei; Emmanuel Owusu; Emmanuel Kobia-Acquah; Emmanuella Esi Dadzie; Emmanuel Anarfi; Seth Wanye (PLoS ONE, 2021)
Suboptimal cataract surgery outcomes remain a challenge in most developing countries. In Ghana, about 2 million people have been reported to be blind due to cataract with about 20% new cases being recorded yearly. The aim of this study was to evaluate postoperative correction of refractive errors after cataract surgery in a selected eye hospital in Ashanti Region, Ghana. This was a retrospective study where medical records of patients (aged 40-100) who reported to an eye hospital in Ghana from 2013-2018 were reviewed. Included in the study were patients aged ≥40 years and patients with complete records. Data on patient demographics, type of surgery, intra-ocular lens (PCIOL) power, availability of biometry, postoperative refraction outcomes, pre- and postoperative visual acuity were analyzed. Data of two hundred and thirteen eyes of 190 patients who met the inclusion criteria were analyzed. Descriptive analysis and Chi-square test were carried out to determine the mean, median, standard deviation and relevant associations. The mean ± SD age was 67.21±12.2 years (51.2% were females). Small Incision Cataract Surgery (99.5%) with 100% IOL implants was the main cataract surgery procedure in this study. Pre-operative biometry was performed for 38.9% of all patients on their first eye surgery and 41.5% for second eye surgeries. About 71% eyes in this study were blind (presenting VA<3/60) before surgery; 40.4% had post-operative VA <3/60. Pre-existing ocular comorbidities discovered post- surgery, attributed to suboptimal visual outcomes. More than half (55.3%) of patients did not undergo postoperative refraction due to loss to follow-up. Year of surgery (p = .017), follow up visits< 2months (p < .0001) and discovered comorbidity post-surgery (p = .035) were the factors significantly associated with postoperative refraction. Myopia and compound myopic astigmatism were the dominant refractive error outcomes. The timing of post-operative refraction had a significant effect on postoperative refraction done. These findings indicate a clinically meaningful significance between completion of postoperative care and postoperative refraction done. Consequently, with settings in most developing countries, where less biometry is done, it is appropriate that post-operative refractive services are encouraged and done earlier to enhance the patients' expectations while increasing cataract surgery patronage.